Lightweight and secure D2D group communication for wireless IoT - Miao, Junfeng; Wang, Zhaoshun; Xue, Xingsi; Wang, Mei; Lv, Jianhui; Li, Min (Frontiers in Physics, 2023)
In recent years, wirless Internet of things (IoT) technology has developed rapidly, and the reuse of spectrum resources, network efficiency, and the diversity of multi-communication scenarios have brought great challenges to the existing Internet of Things. And Device to Device (D2D) communication technology in 5th Generation Mobile Communication Technology (5G) has good application prospects in these aspects. Therefore, the combination with D2D can well solve the needs in the wirless Internet of things. However, safe and effective communication has become an urgent problem to be solved. In this paper, This paper proposes a D2D group communication protocol for wireless IoT in 5G. In this protocol, the Chinese remainder theorem is introduced into the protocol design, and a secure and efficient group authentication scheme is constructed based on secret sharing and Chebyshev polynomial. The formal security proof using Burrows Abadi Needham(BAN) logic and informal security analysis show that our proposed protocol meets the security requirements. Through performance analysis, compared with other related schemes, this scheme not only provides better security, but also the computation overhead has increased by 83% and the communication overhead has increased by 51%.